2013
DOI: 10.1017/s1751731113000165
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bacterial community shifts in the gastrointestinal tract of pigs fed diets supplemented with β-glucan from Laminaria digitata, Laminaria hyperborea and Saccharomyces cerevisiae

Abstract: This study was designed to evaluate the effects of algal and yeast b-glucans on the porcine gastrointestinal microbiota, specifically the community of Lactobacillus, Bifidobacterium and coliforms. A total of 48 pigs were fed four diets over a 28-day period to determine the effect that each had on these communities. The control diet consisted of wheat and soya bean meal. The remaining three diets contained wheat and soya bean meal supplemented with b-glucan at 250 g/tonne from Laminaria digitata, Laminaria hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 49 publications
(81 reference statements)
3
20
1
Order By: Relevance
“…According to this study, cultivable Bacteroides was negatively affected in polypectomized patients after intake of barley ␤-glucans (27). In vitro and animal trials support that Enterobacteriaceae could not utilize ␤-glucans (20,25,50). According to in vitro and animal trials, this study showed a significant reduction in cultivable Enterobacteriaceae and total coliforms.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…According to this study, cultivable Bacteroides was negatively affected in polypectomized patients after intake of barley ␤-glucans (27). In vitro and animal trials support that Enterobacteriaceae could not utilize ␤-glucans (20,25,50). According to in vitro and animal trials, this study showed a significant reduction in cultivable Enterobacteriaceae and total coliforms.…”
Section: Discussionmentioning
confidence: 61%
“…An increased level of lactobacilli was found in animal models after a barley-or oat-containing diet, especially using high-viscosity ␤-glucans (22,23,24). At the same time, an oat product-based diet or ␤-glucans from Laminaria digitata, Laminaria hyperborea, and Saccharomyces cerevisiae did not increase the levels of lactobacilli in pigs and rats (25,50). Taken together, these results suggested that the prebiotic potential of whole-grain barley/␤-glucan was not always reproducible in vivo.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…(Jaskari et al, 1998). More recently, Laminaria spp.-derived laminarin has been shown to increase intestinal Lactobacilli numbers in weaned pigs and also reduce coliforms (Murphy et al, 2013). Fucoidan has also been shown to have prebiotic effects in the porcine monogastric model (Lynch et al, 2010;Sweeney et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…b-glucan can benefit host, including mirror carp (Cyprinus carpio L.) [19], pig [20], juvenile beluga (Huso huso) [21] and broilers [22], by selectively stimulating the growth and/or activity of one or certain microbial genera/species. This study evaluated the intestinal microbiota in sea cucumber response to dietary b-glucan supplementation.…”
Section: Discussionmentioning
confidence: 99%